THE ESSENTIAL OF SEMAR POWER IN THE PLAY OF BATHARA KALA TUNDHUNG-SURYA NDADARI BY KI MANTEB SUDARSONO - Lestari, Dewi Dian; Darmoko, Darmoko (International Review of Humanities Studies, 2023)
This paper discusses the essential of Semar Power in the puppet play entitled Bathara Kala Tundhung-Surya Ndadari. The play Bathara Kala Tundhung-Surya Ndadari was taken into consideration in conducting this research because it is a unique play, namely the Ruwat play and the Mahabharata story play which were united through the experience of the presence of Semar characters in a puppet play by Ki Manteb Sudarsono. The main problem in this research is how the essence of Semar Power is formulated in Batara Kala Tundhung-Surya Ndadari. This study aims to formalize Semar's power as the holder of the superiority of power in the play Bathara Kala Tundhung-Surya Ndadari. This research is a qualitative descriptive study with an objective approach that aims to explore and describe the essential of Semar power by the researcher as the main instrument in data collection. The conceptual framework used in this research is a conceptual framework according to Javanese Ethics. The results of this study indicate that the essence of Semar Power is power attached to the status and role above as a pamong of Pandawa, the status as danyang of the land of Java through assistance in carrying out ruwatan, and the role of a god who thwarts the Batara Guru test for Pandawa in Baratayuda. Based on this research, it can be stated that the power of Semar is related to the status and role to eliminate all threats over the power of rage, restore the evil power to its place and maintain the stability of the world and the universe, Memayu hayuning bawana.